Endobronchial coils for severe emphysema are effective up to 12 months following treatment: medium term and cross-over results from a randomised controlled trial. - Zaid Zoumot; Samuel V Kemp; Suveer Singh; Stephen R Bicknell; William H McNulty; Nicholas S Hopkinson; Ewen T Ross; Pallav L Shah (PLoS ONE)
Background There is a clinical need for therapeutic options to reduce hyperinflation associated with severe emphysema. Endobronchial Coils (coils) are nitinol devices implanted bronchoscopically under fluoroscopic guidance to re-tension the lung. We report the medium term effectiveness and safety of coils in a study of patients with emphysema. Methods Forty five subjects with severe airflow obstruction and hyperinflation received bilateral sequential treatment with coils (30 day interval between treatments) as part of a randomised controlled trial with a primary endpoint 90 days after the final treatment (Clinicaltrials.gov NCT01334307). Further assessments were made at 180 and 360 days and in this study the primary outcome was the effect of coil treatment on the St. George's Respiratory Questionnaire (SGRQ) 360 days following treatment. Results At 360 days following treatment, there was an improvement in the SGRQ score of -6.1±14.0 points (p = 0.01) compared to baseline. Improvements in secondary outcomes were seen with increases in forced expiratory volume in the first second of 8.9 ±22.2% (p = 0.002) and 6-minute walking distance of 34.1±52.4m (p = 0.003). The safety profile was acceptable out to 360 days post-treatment. Conclusions Statistically and clinically meaningful benefits in quality of life, exercise capacity and pulmonary function in patients treated with coils are sustained twelve months after treatment. Trial registration information Clinicaltrials.gov NCT01334307.